Analysis of Influence of Profitability, Solvability, Liquidity and Public Ownership on Delay of Financial Report Publication - Dyah Febriantina Istiqomah (Program Pendidikan Vokasi Universitas Brawijaya, 2013)
This study aims to test the influence of profitability, solvability, liquidity and public ownership on delay of financial report publication. The sample is 51 non-manufacture companies listed in Indonesian Stock Exchange which are selected by using purposive sampling method. This study was tested by using multiple regression. The result shows that profitability, solvability, and liquidity influence the delay of financial report publication. However, ownership does not influence the delay of financial report publication.